Aprovechamiento de los subproductos de brócoli (Brassica oleracea var. Itálica) y de la remolacha (Beta Vulgaris), para la elaboración de una pasta. - Lara Atiaja, Karina Gabriela (2023)
The present research work was carried out to take advantage of the by-products of broccoli (Brassica oleracea var. Itálica) and of the beetroot (Beta vulgaris), to make a paste, through a physical, chemical, microbiological, sensory, and statistical analysis that to obtain a product suitable for human consumption. For this project, a completely randomized block experimental design (DBCA) with two a×b factors were applied. Factor a with five levels and factor b with two levels giving a total of twenty treatments under study. The statistical analysis of all the study variables was carried out in the Infostat statistical program, allowing the identification of the experimental treatment (T2) a1b2 as the best in terms of physicochemical characteristics, being composed of 30% broccoli stalk flour + 70% flour. of wheat with a drying time of 30 minutes. The same one that presents the average values referred to in percentage such as: Moisture, 21.19, Protein 2.10%, Fat 5.64%, Ash 1.9%, Fiber 1.22%, Total carbohydrates 62.25%, Energy 310.6 kcal/ 100g. The results of the physicochemical analyses determined that the product is within the standards that are described in the standard (NTE INEN 1 375). For the acceptability analysis carried out on 10 testers, we found that consumers prefer the T8(a4b2) treatment that contains 20% broccoli stalk flour + 10% beet husk flour + 70% wheat flour with a drying time of 30 min evaluated from the attributes of color, smell, flavor, texture, and stickiness. Given the case that we have 2 best treatments, we proceed to consider the best treatment the same one that meets the parameters required by the regulations (NTE INEN 1 375). The same one that corresponds to T2(a1b2) and that microbiologically analyzed presents the following results for the mesophilic aerobic count 7.0 x 101 where the reference value is 3.0 x 105. Regarding the coliform count, E. coli and Staphylococcus aureus remain at <10 results, much lower than those of the reference value 1.0 x 102. While the presence of Salmonella spp was not detected as required by the standard (NTE INEN 1 375).